الأغنية الشعبية ومسايرتها لمرحلة البناء الاشتراكي في الجزائر - إلهام منصوري (My University, 2023)
Summary: Folk song is considered a type of popular literature that embodied for us the events of the past with its dates and details, and this is what made it truer and more accurate than history. Its locations varied and varied from one region to another, and it was passed down from generation to generation through word of mouth. It was like an outlet through which the individual expressed his feelings and hopes. And his ambition, and his social, cultural, economic and political reality. --------------------- الملخص: تعتبر الأغنية الشعبية نوع من أنواع الأدب الشعبي الذي جسد لنا أحداث الماضي بتواريخه وتفاصيله وهذا ما جعلها أصدق وأدق من التاريخ، اختلفت وتنوعت مواضعها من منطقة إلى أخرى، وتوارثت من جيل إلى جيل عن طريق المشافهة، وكانت مثل المتنفس الذي يعبر به الفرد عن أحاسيسه وآماله وطموحه، وعن واقعه الاجتماعي والثقافي والاقتصادي والسياسي ----------------------- Résumé: La chanson populaire est considérée comme un type de littérature populaire qui incarne pour nous les événements du passé avec ses dates et ses détails, et c'est ce qui la rend plus vraie et plus précise que l'histoire. Et son ambition, et son impact social, culturel, économique et réalité politique.
Keywords: song; popularity; history; orality; أغنية، الشعبية، تاريخ، المشافهة; chanson; folklore; histoire; bouche à oreille